Comparison of binaural auralisations to a real loudspeaker in an audiovisual virtual classroom scenario: effect of room acoustic simulation, HRTF dataset, and head-mounted display on room acoustic perception* - Stärz Felix; Van De Par Steven; Roßkopf Sarah; Kroczek Leon O. H.; Mühlberger Andreas; Blau Matthias (Acta Acustica)
In this study, auralisations of a real room were compared to the actual acoustics of that room using listening tests. Participants sat in a room and wore a combination of a head-mounted display (HMD) and headphones, and rated different room-acoustic attributes for an auralised loudspeaker and the corresponding real loudspeaker in the room, without knowing what they were actually listening to. Auralisations were created with varying levels of detail using either measured or simulated binaural room impulse responses (BRIRs), which were based on individual or generic Head-and-Torso simulator (HATS) data. Besides different levels of detail, some manipulations of the room acoustics were introduced into the simulation to better contextualise the results. The results show a good agreement between the auralised and the real room for both measured and simulated BRIRs. The observed deviations based on the different levels of detail were generally smaller than the introduced room acoustic manipulations. Individual head-related transfer function (HRTF) data had no real benefit, and the passive influence of the HMD headphone combination had no effect on the ratings.